An Atypical Presentation of Hirayama Disease With Lower Limb Myelopathic Symptoms Only. (December 2021) - Mattson, Laura M.; Alomar-Jimenez, Walter O.; Hearn, Sandra L.
Abstract : Abstract: Hirayama disease is a rare neuromuscular disease, which classically presents as lower motor neuron weakness and atrophy in the upper limbs and specifically the C7–T1 myotomes. Proposed pathogenesis relates to microcirculatory dysfunction in the territory of the anterior spinal artery caused by epidural venous plexus engorgement with forward displacement of the posterior dura and spinal cord during neck flexion, leading to chronic ischemic changes in the lower cervical anterior horn cells. Diagnosis hinges upon clinical and radiographic findings, and treatment is generally conservative given the self-limited nature of the disease. Here, we present a case with classic radiologic findings of Hirayama disease with lower limb myelopathic findings alone. This case raises the question of whether the pathophysiology leading to focal anterior cervical myelopathy in forward flexion could present along a broader clinical spectrum than previously recognized, from complete asymptomaticity, to classic Hirayama disease with C7–T1 atrophy, to cervical myelopathy with long tract signs. Abstract : Supplemental digital content is available in the text.